August E. Grant, Amanda F. C. Sturgill, Chiung Hwang Chen, and Daniel A. Stout, eds., Religion Online: How Digital Technology is Changing the Way We Worship and Pray: Praeger, 2019 (Homiletic, 2019)
Please click the PDF button to access the review.